PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN LEARNING CYCLE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII DI SMPN 2 AMPEK NAGARI KAB. AGAM - Loka, Lola Fitria (STKIP PGRI Sumbar, 2014)
This research is motivated by the lack of student learning outcomes for students are less active andless motivated in learning activities. Teachers tend to use strategies that vary in saturation and learning so thatstudents are less motivated to learn. One of the materials that get results of study under minimum completenesscriteria (KKM) is the material of ecosystems. This study aims to determine the effect of the use of learningstrategies on learning outcomes learning cycle biology class students 2 Ampek Nagari Agam district. Thisresearch is experimental research study design randomized control posttest-only design. The population in thisstudy were all students of class VII SMP 2 Ampek Nagari Agam district listed in the 2nd half of the school year2013/2014. Sampling was done by purposive sampling. Based on the sampling obtained in VII.3 class as theexperimental class and the control class as a class VII.2. This study was conducted in May 2014. The data havebeen analyzed using t-test at 95% confidence level (Î±= o, 05). Prior to the t-test, the normality test aimed to seeif the two groups of samples are normally distributed. After the normality test, the homogeneity test aimed to seewhether the two groups both samples have a homogeneous variance. When both normal and homogeneoussample t-test is carried out to test the hypothesis. The results showed that student learning outcomesexperimental class higher than the control class. Based on the hypothesis test and t-test obtained count rates thitung(1,96 > ttabel (1,67) This means that the hypothesis is accepted, it can be concluded Learning Cycle use learningstrategies to improve learning outcomes biology class VII SMPN 2 Ampek Nagari Agam district.